Revitalizing Green Tourism Villages Through Strengthening Community Ecosystem to Achieve Sustainable Tourism in Bilebante Village, Lombok - Putria Sri Handayani; Yustina Denik Risyanti; Sapto Supriyanto (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to analyze the role of the community in preserving culture, improving the economy and protecting the environment as well as analyzing the role of the village government in encouraging profitable and sustainable tourism in the green tourism village of Bilebante, Lombok. Method: Through a Descriptive Qualitative approach with a research period from September 2024 – February 2025. Determination of informants using Purposive Sampling techniques, while data sources in the study were obtained from primary and secondary data and data collection techniques through observation, interviews and documentation. Result: Research results show that collaboration between communities, such as Pokdarwis (Tourism Groups), and the village government has promoted sustainable tourism that preserves traditions and the environment, while positively impacting the community. This collaboration includes the formation of an Ecorangers team and training for business owners in the green tourism village of Bilebante, Lombok. Contribution: The important contributions of this research have brought about significant changes in the preservation of traditions and the environment, as well as creating tourism that positively impacts communities and the environment that were once threatened by modernization. These tourism development efforts have created sustainable tourism that positively impacts communities and the environment for the future.